Learning Styles and School Adjustments among Secondary School Students - Maharjan, Rocky (Mangal Research Journal, 2020)
Learning style is individual's preferred way of processing new information for efficient learning. Students whose learning styles are compatible with the teaching style of a course instructor tend to retain information longer, apply it more effectively, and have more positive post-course attitudes toward the subject than do their counterparts who experience learning/teaching style mismatches. The purpose of this study was to study the relationship of gender and school type in school adjustment as well as learning styles and to explore the effect of learning style in school adjustment. The study was carried out among 200 students selected from government (n=100) school and private school (n=100). The Learning Style Inventory (LSI) and Adjustment Inventory for School Students (AISS) were used to collect the data. The data obtained from survey was analyzed by using group statistics, independent sample test, chi square test and ANOVA. The study found that most of the students both boys and girls had divergent learning styles. The independent t test showed that students from private schools were significantly poor in emotional and educational adjustment than students from government schools. The ANOVA test revealed that effects of learning styles were significant in emotional, social and overall school adjustment but not significant on educational adjustment.